Metastable Decoherence-Free Subspace and Pointer States in Mesoscopic Quantum Systems - Retamal-Abarzua, J; Lopez-Cabrera, C (American Physical Society, 2018)
Two initially correlated coherent states, each interacting with its own independent dissipative environment, exhibit a sudden transition from classical to quantum decoherence. This change in the dynamics is a turning point in the decoherence in the sense that depending on the average number of photons of each harmonic oscillator, decoherence can even be suppressed. Indeed, the quantum state is time independent for a time span in the mesoscopic regime, revealing a decoherence-free subspace. Furthermore, the absence of decoherence is manifested in the apparition of a metastable pointer-state basis. © 2018 American Physical Society.